PEMETAAN POTENSI WISATA ALAM SEKITAR KHDTK UNIVERSITAS LAMBUNG MANGKURAT PROVINSI KALIMANTAN SELATAN - Andi Harahap; Abdi Fithria; Khairun Nisa (Universitas Lambung Mangkurat, 2020)
Tourism potential in South Kalimantan has many natural tourism potentials that many. Specially Designed Forest Area (KHDTK) is a forest area designated for research and development, education and training purposes as well as local religious and cultural interests. KHDTK not only serves as a research, education and training location but also has enormous tourism potential to be developed so that its expectation can add tourist attraction to visit the tourist object. KHDTK ULM as one of the alternative objects of attraction Nature tourism, need mapping of analysis of tourism potential in the region.1The research1method used in this research1is1descriptive and quantitative1research method with survey1technique. Incidental sampling is used in a sample determination technique based on anyone who by chance / incidental meet can be used as a sample matching the data source. The result obtained that tourist attraction object in KHDTK ULM spread at altitude 85 - 471 mdpl, on land cover of open space, agriculture and secondary forest. Potential objects of tourist attraction in KHDTK ULM include: outbound, dukuh gardens, swimming dutch, Dutch fort, great hilltop, waterfall and sambar deer breeding. The result of the most tourist attraction attraction in the interest of tourists is a large hilltop.Keywords ; Potential Mapping; Natural Touris; KHDTK ULM